Effect of Addition of Green Propolis on Microbiological and Shear Properties of Ionomer Cement - , Aline Aparecida dos Santos; , Ana Cláudia Oliveira Teles; , Roberto de Souza Teodoro Junior; , Larissa Doalla de Almeida e Silva; , Carolina Carvalho de Oliveira Santos; , Thiago Fonseca-Silva (Archives of Current Research International, 2025)
Aims: To modify the GIC with green propolis extract to evaluate its antimicrobial and shear strength effects. Study Design: This is an experimental, In vitro study. Place and Duration of Study: The stages of this project were carried out at the Department of Dentistry of the Federal University of the Jequitinhonha and Mucuri Valleys, in the city of Diamantina/MG, Brazil. Methodology: For the microbiological analysis, cement discs were prepared in triplicate and grouped into four groups (GIC without modification, GIC+1% propolis extract, GIC+5% propolis extract, GIC+10% propolis extract). Azithromycin at 10% was used as a positive control, and GIC without modification was used as a negative control. The discs were embedded in petri dishes containing BHI agar and dental biofilm inoculum. The plates were then placed in an oven at 36°C for 24 hours. The results obtained in the microbiological evaluation were used to define the composition of the groups for the shear tests. Three groups were formed (GIC + 5% propolis extract, GIC + 10% propolis extract and GIC without modification) and the cements were used to bond orthodontic buttons to the enamel surface (n=10 in each group). The specimens were then placed in a container with distilled water and kept at 36°C for 24 hours. The EZ-Test-Shimadzu® universal testing machine was used to perform the mechanical tests. The collected data were tabulated in the SPSS 17.0 sofware for Windows. Results: The results showed that the GIC modified with 5% and 10% propolis presented an inhibition zone, proportionally compatible with the positive control. Furthermore, the GIC modified with 10% propolis extract demonstrated greater shear strength when compared to the unmodified GIC. Conclusion: The GIC modified with 10% propolis extract presents an increase in the shear strength of the cement in addition to enhanced antimicrobial effects.